Patterns of landscape change in a rapidly urbanizing mountain region - Clémence Vannier; Jérémie Lefebvre; Pierre-Yves Longaretti; Sandra Lavorel (Cybergeo)
We describe landscape changes in the context of a rapidly urbanizing mountain region, around the city of Grenoble in the French Alps. By combining a multi-source merging method and aerial photo-interpretation, we analyzed land cover dynamics during the 1998-2009 period. The analysis across 3 dates of the cartographic database for the 4450km² at 1:15,000 scale, with of 23 land cover types, showed a rapid and steady urban growth at the expense of agricultural areas, with an expansion greater than 6% during the ten-year period. A synthetic overview of changes at municipality scale showed the prominence of newly artificialized areas not only in the valleys around Grenoble but also in the main, predominantly agricultural plain areas of Bièvre and Voiron. Most of the changes are contiguous to already urbanized areas. Therefore they induce limited landscape fragmentation, as new built-up areas are emerging alongside existing ones or within existing ones as part of a densification process.The results obtained for this area illustrate an emerging major preoccupation in the Western European Alps (Switzerland, Italy, Austria...), namely that the present rate of urbanization is not sustainable in the longer run in fragile Alpine valleys. In this respect, our cartographic database will provide baseline information for a participatory prospective exercise performed with local stakeholders of the Grenoble region, aiming to support sustainable land management and planning.